Household Food Security Analysis Case Study on Sustainable Food House Area Program (KRPL) in Bandungrejosari Village, Sukun District, Malang - Tartila Fitri; Iid Mufaidah; Nuhfil Hanani; Hery Toiba (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
The population of Indonesia increases every year, so there is an increase in demand for food, both commodities of grain, vegetables, fruit and others. If the demand for food continues to increase and is not supported by increasing food production there will also be food insecurity at certain times. The government's policy to overcome this problem is the Acceleration of Food Consumption Diversification (P2KP) and its program namely Sustainable Food House Area (KRPL). The purpose of this study is to analyze household food security using a quantitative aspect approach (TKE and TKP) and quality aspects (PPH score) The results of the study PPH scores achieved by KRPL participating households and not KRPL participants were 86.6 and 75.9, respectively. This value shows the pattern of food consumption that has not varied. However, it can be seen that participating households of KRPL have more food consumption than households not participating in KRPL While the energy consumption and non-participant household protein of KRPL still have not reached the consumption recommendations set by the government, amounting to 1883.5 kcal / capita / day and 49.7 gram / capita / day.